A comprehensive computational fluid dynamics simulation on the air distribution in an operating room at University of Malaya Medical Centre Malaysia - Yau, Yat Huang; Ding, L.C. (SAGE Publications, 2015)
A practical case study on the air distribution in an operating room (OR) at University of Malaya Medical Centre, Kuala Lumpur is presented. The OR has a relatively large floor area since it is connected with the medical storage room and served by a total of 14 room air inlets and 3 exhausts. The room air inlets are located at the peripheral of the surgical site rather than just above the surgical site. From the measurement conducted, the average room inlet air velocity was 0.19 m/s with a standard deviation of 0.03 m/s for all inlets and 33.5 air change per hour. In line with its current design, the air distribution was simulated using the computational fluid dynamics software. Initial simulation with the room air inlet velocity of 0.2 m/s showed an improper airflow at the surgical site. However, this condition was not significantly improved even by doubling the inlet velocity. The results have identified that with air inlets located at the peripheral of surgical site, the air inlet design was unable to provide a satisfactory airflow across the surgical site, and hence not appropriate for the purpose of its intended use.